Redescription, Morphogenesis, and Molecular Phylogeny of Pseudosincirra longicirrata nov. comb., With Establishment of a New Genus Pseudosincirra nov. gen. (Ciliophora, Hypotrichia) - Gao, Qi; Shao, Chen; Tang, Qiuyue; Li, Jingbao (Frontiers in Microbiology, 2021)
The morphology and morphogenesis of Pseudosincirra longicirrata nov. gen., nov. comb. isolated from southern China, were investigated with living observation and protargol staining. Our population is similar to the original population in living characteristics and ciliary patterns. The main determinable morphogenetic features of Pseudosincirra longicirrata nov. comb. are the presence of five frontoventral-transverse cirral anlagen (FVT-anlagen) and a dorsomarginal kinety anlage. According to the origin of FVT-anlagen IV and V in proter, it can be determined that P. longicirrata nov. comb. possess two frontoventral rows and one right marginal row. Hence, a new genus, Pseudosincirra nov. gen., is proposed and the diagnosis of Pseudosincirra longicirrata nov. comb. is improved. The new genus is diagnosed as: adoral zone of membranelles and undulating membranes in Gonostomum-pattern; three enlarged frontal cirri, one buccal cirrus and one parabuccal cirrus, postperistomial cirrus and transverse cirri lacking, two more or less long frontoventral rows, one right and two or more left marginal rows, cirri within all rows very widely spaced, dorsal kinety pattern of Urosomoida-type, that is, three dorsal kineties and one dorsomarginal kinety, caudal cirri present. Phylogenetic analyses based on the small subunit ribosomal (SSU rDNA) sequence data indicate that P. longicirrata nov. comb. clusters with Deviata and Perisincirra. It is considered that Pseudosincirra nov. gen. and Perisincirra paucicirrata should be assigned to the family Deviatidae; fine cirri, and cirri within all rows being relatively widely spaced, should be considered as plesiomorphies of Deviatidae; and Deviatidae is closely related to Dorsomarginalia or Strongylidium–Hemiamphisiella–Pseudouroleptus.